GPR119: a promising target for nonalcoholic fatty liver disease. Issue 1 (23rd September 2015) - Yang, Jin Won; Kim, Hyo Seon; Im, Ji Hye; Kim, Ji Won; Jun, Dae Won; Lim, Sung Chul; Lee, Kyeong; Choi, Jong Min; Kim, Sang Kyum; Kang, Keon Wook
ABSTRACT: Nonalcoholic fatty liver disease is associated with metabolic syndrome and has the unique characteristic of excess lipid accumulation in liver. G‐protein‐coupled receptor 119 (GPR119) is a promising target for type 2 diabetes. However, the role of GPR119 activation in hepatic steatosis and its precise mechanism has not been investigated. In primary cultured hepatocytes from wild‐type and GPR119 knockout (KO) mice, expression of lipogenic enzymes was elevated in GPR119 KO hepatocytes. Treatment of hepatocytes and HepG2 cells with GPR119 agonists in phase 2 clinical trials (MBX‐2982 [MBX] and GSK1292263) inhibited protein expression of both nuclear and total sterol regulatory element binding protein (SREBP)‐1, a key lipogenesis transcription factor. Oral administration of MBX in mice fed a high‐fat diet potently inhibited hepatic lipid accumulation and expression levels of SREBP‐1 and lipogenesis‐related genes, whereas the hepatic antilipogenesis effects of MBX were abolished in GPR119 KO mice. MBX activated AMPK and increased Ser‐372 phosphorylation of SREBP‐1c, an inhibitory form of SREBP‐1c. Moreover, inhibition of AMPK recovered MBX‐induced down‐regulation of SREBP‐1. These findings demonstrate for the first time that the GPR119 ligand alleviates hepatic steatosis by inhibiting SREBP‐1‐mediated lipogenesis in hepatocytes.—Yang, J. W., Kim, H. S., Im, J. H., Kim, J.W., Jun, D. W., Lim, S.C., Lee, K., Choi, J. M., Kim, S.K., Kang, K.W.GPR119: a promising target for nonalcoholic fatty liver disease. FASEB J. 30, 324‐335 (2016). www.fasebj.org